A novel method for measuring pulmonary artery pressure by high-frequency ultrasound-guided transthoracic puncture in rats - Zhang, Xiaofeng; Li, Jingtao; Zeng, Decai; Liang, Chunting; Zhong, Yanfen; Huang, Tongtong; Mo, Yingying; Rao, Huaqing; Pan, Xiaoxiong; Wu, Ji (Frontiers in Cardiovascular Medicine, 2022)
Objectives The success of the rat model of pulmonary hypertension (PH) is primarily dependent on the measurement of pulmonary artery pressure. We herein demonstrate a novel method for measuring pulmonary artery pressure through a high-frequency ultrasound-guided transthoracic puncture in rats. The efficacy and time of this novel method are also discussed. Methods A single subcutaneous injection of monocrotaline (MCT) was used to establish a rat model of PH. Through the heat shaping method, the tip of that puncture cannula was maintained at a certain angle after the needle core was removed. In-plane real-time guided trocar puncture of the right ventricular outflow tract was performed in the short-axis section of the parasternal aorta. The external pressure sensor was used to record the real-time waveform of right ventricular systolic pressure, pulmonary artery systolic pressure, and diastolic pressure. Results The success rates of which using this novel method in the model group and the control group were 88.5 and 86.7%, respectively. The time of puncture pressure measurement was 164 ± 31 and 235 ± 50 s, respectively. The right ventricular systolic blood pressure, pulmonary systolic blood pressure, and diastolic blood pressure of the model group were higher than those of the control group. Conclusion The modified method for trocar is helpful for accurately positioning pulmonary artery manometry. The method described in this paper has a high success rate and short operation time. It can simultaneously measure systolic blood pressure, diastolic blood pressure, and mean pressure of the right ventricle and pulmonary artery. It has a broad application prospect in verifying the rat PH model and pulmonary artery pressure monitoring.